2016
DOI: 10.1016/j.optlaseng.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

High-quality 3D shape measurement using saturated fringe patterns

Abstract: This paper proposes a method to potentially conquer one of the challenges in the optical metrology community: optically measuring three-dimensional (3D) objects with high surface contrast. We discover that for digitally equally phase-shifted fringe patterns, if the fringe period P is an even number, the N = P/2 × k, (k = 1, 2, 3,. . .) step algorithm can accurately recover phase even if the fringe patterns are saturated; and if P is an odd number, N = P × k step algorithm can also accurately recover phase even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 23 publications
(23 reference statements)
0
23
0
Order By: Relevance
“…In order to verify the feasibility of the proposed method, numerical simulations were carried out. We simulated different amount of saturation by a scale factor S [21][22] . For the regular fringe patterns, the k-th ideal 8-bit fringe patterns for a N-step generalized phase-shifting algorithm can be described as, (12) Where p is the period of fringe patterns, k  is the arbitrary phase-step, ) , ( y x  is the phase to be retrieved, and the Peaks function of MATLAB was used to represent the phase corresponding to the measured object.…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to verify the feasibility of the proposed method, numerical simulations were carried out. We simulated different amount of saturation by a scale factor S [21][22] . For the regular fringe patterns, the k-th ideal 8-bit fringe patterns for a N-step generalized phase-shifting algorithm can be described as, (12) Where p is the period of fringe patterns, k  is the arbitrary phase-step, ) , ( y x  is the phase to be retrieved, and the Peaks function of MATLAB was used to represent the phase corresponding to the measured object.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Basel et al [21] proposed a multi-polarization fringe projection (MPFP) imaging technique that eliminates saturated points and enhances the fringe contrast by selecting proper polarized channel measurements, but it needs expensive polarization cameras. Chen et al [22] measured high dynamic range shapes directly using saturated fringes, but many fringe patterns are needed. Recently, Jiang et al [23] proposed a high dynamic range real-time 3D shape measurement method without changing camera exposures.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [25], it can measure the shiny surfaces regardless of the saturation level, but it requires the acquisition of many patterns, slowing down the measurement process. To deal with overexposure in the captured fringe pattern image, Ref.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen et al [26] found that the phase-shifting methods can overcome the image saturation if the number of the phase shift is high enough so that at least three unsaturated fringe intensities can be recorded successfully. Moreover, Chen et al [27] proposed a technique, by which the phase is also calculated from raw phase-shifting images but without considering whether they are saturated or not. Hu et al [28,29] introduced a phase-shifting based method by taking advantage of no less than three unsaturated fringe image from standard N -step phase-shifting algorithm.…”
Section: Introductionmentioning
confidence: 99%